2021
DOI: 10.1186/s13059-020-02251-5
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between codon optimality and cis-regulatory elements dictates mRNA stability

Abstract: Background The regulation of messenger RNA (mRNA) stability has a profound impact on gene expression dynamics during embryogenesis. For example, in animals, maternally deposited mRNAs are degraded after fertilization to enable new developmental trajectories. Regulatory sequences in 3′ untranslated regions (3′UTRs) have long been considered the central determinants of mRNA stability. However, recent work indicates that the coding sequence also possesses regulatory information. Specifically, tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
75
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 69 publications
(129 reference statements)
0
75
0
Order By: Relevance
“…Besides, FTO has also been found to play a crucial role in the early development of the human central nervous system, and cardiovascular system (28). In recent years, most studies showed there are interactions between miRNAs with m6A in the regulation of messenger RNA (mRNA) stability (29). Even the regulation between themselves is present in several studies (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, FTO has also been found to play a crucial role in the early development of the human central nervous system, and cardiovascular system (28). In recent years, most studies showed there are interactions between miRNAs with m6A in the regulation of messenger RNA (mRNA) stability (29). Even the regulation between themselves is present in several studies (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…These analyses took advantage of averaging codon effects in multiple different positions on the transcriptome. However, the correlation tended to be modest in part due to the presence of factors that affect mRNA stability independent of codons (e.g., RNA-binding proteins and microRNAs) (Medina-Muñoz et al, 2021). The ORFome approach minimizes this disadvantage by fixing the 5´ and 3´ UTR sequences, yet it also depends on a correlation study, and its target is limited to endogenous mRNA sequences that are under evolutionary constraints (Bazzini et al, 2016;Narula et al, 2019;Wu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that translation strongly affects mRNA stability in cis in a codon-dependent manner in vertebrates (Bazzini et al, 2016;Mishima & Tomari, 2016; as well as in other species (Boël et al, 2016;Burow et al, 2018;de Freitas Nascimento et al, 2018;Harigaya & Parker, 2016;Jeacock, Faria, & Horn, 2018;Presnyak et al, 2015;Radhakrishnan et al, 2016), a process referred as codon optimality (Presnyak et al, 2015). Codon optimality is the most pervasive mechanism underlying mRNA stability in yeast (Cheng, Maier, Avsec, Rus, & Gagneur, 2017) and vertebrates (Medina-Muñoz et al, 2021). Specifically, to determine the regulatory strength of codon optimality in vertebrates, we have recently developed a machine learning model that predicts mRNA stability based on codon composition (Medina-Muñoz et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Codon optimality is the most pervasive mechanism underlying mRNA stability in yeast (Cheng, Maier, Avsec, Rus, & Gagneur, 2017) and vertebrates (Medina-Muñoz et al, 2021). Specifically, to determine the regulatory strength of codon optimality in vertebrates, we have recently developed a machine learning model that predicts mRNA stability based on codon composition (Medina-Muñoz et al, 2021). Trained with multiple profiles of mRNA stability for thousands of genes obtained from human (Q.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation